Talent Management in the Hospitality Sector: Predicting Discretionary Work Behaviour - Friday Ogbu Edeh; Nurul Mohammad Zayed; Iryna Perevozova; Halyna Kryshtal; Vitalii Nitsenko (Administrative Sciences, 2022)
Hospitality organisations have suffered a lot of setbacks, such as low performance caused by the COVID-19 pandemic, during which most management took drastic decisions to retrench talent, and these decisions have engendered low discretionary work behaviour and low emotional labour display amongst its talent. These maladies would have been averted if talent management practices were implemented effectively by hospitality organisations. It is based on this premise that this study investigates the effect of talent management on discretionary work behaviour in hospitality organisations in Nigeria using a survey research design. A sample frame of 820 was drawn from 60 registered hospitality organisations in the south-eastern part of Nigeria. A sample size of 263 was drawn from the sample frame. Linear regression was employed to analyse the formulated hypotheses with the aid of IBM statistical package for the social sciences version 20.0. The findings of the study show that talent management dimensions have significant effects on discretionary work behaviour in hospitality organisations in Nigeria. The study concludes that talent management measured in terms of talent attraction, talent development and talent retention have significant effects on the indicators of discretionary work behaviour. The study recommends that human resource professionals and organisational leaders should utilize talent management as a strategy to enhance discretionary work behaviour in their respective organisations.